2019
DOI: 10.9734/jaeri/2019/v19i330086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Weights and Sowing Media on Germination and Early Growth of Afzelia africana Smith ex Pers

Abstract: Seed weight is essential in assessing seed quality traits, while sowing medium has significant role in seed germination. This study therefore assessed effect of seed weights and sowing media on germination of Afzelia africana seeds to enhancing sustainable production of the species. Seeds of different sizes were collected, weighed and grouped into small (120), medium (120) and large (120) seeds. Each seed group was sown in three sowing media (washed river sand, decomposed sawdust, and forest top soil) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Seeds of Monodora myristica sown in saw dust only had the highest emergence rate when compared to other growth media. This supports the work of Peter-Onoh et al, (2014) which reported that saw dust improved early and high number of Monodora myristica in the nursery, and that of Aderounmu et. al.…”
Section: Resultssupporting
confidence: 90%
“…Seeds of Monodora myristica sown in saw dust only had the highest emergence rate when compared to other growth media. This supports the work of Peter-Onoh et al, (2014) which reported that saw dust improved early and high number of Monodora myristica in the nursery, and that of Aderounmu et. al.…”
Section: Resultssupporting
confidence: 90%
“…Large seeds influenced the seedling height, foliage, leaf area and stem collar diameter. This observation correlates with the findings of Aderounmu et al (2019), Fredrick et al (2020 and Aderounmu et al (2020) who reported the direct association between seed sizes and growth rate of Afzelia africana, Dennettia tripetala and Anacardium occidentale respectively. Singh et al (2021) also reported that larger seeds enhanced more growth in shoot length, collar diameter and root length in some forest tree species.…”
Section: Discussionsupporting
confidence: 90%
“…The variations in nursery growing media emerge from the different soil types and their amendments [12,13]. The influence of the growing media on the performance of commercial tree species is an important factor since it forms the basis of adjustments to tree nursery practices depending on the demands of the species raised [14,15].…”
Section: Introductionmentioning
confidence: 99%